(untitled) (Gragoatá, 2017)
Migration is one of the fundamental and widespread causes of linguistic contact and variation induced by contact. Although contact-induced linguistic variation is not uncommon, it requires explanation within a model that allows the linguistic data to be contextualized in the communicative space. It requires the localization of language variation from the speaker in his/her historical context (with his/her variety repertoire, his/her communicative routines and the effect of this communicative routines in his/her own repertoire). In this sense, the speaker represents a minimal unit of the communicative space (’glossotope’) in which it is inserted. ———————————————————————————————————- Variação linguística induzida por migração no Espaço Comunicativo A migração é uma das causas fundamentais e de propagação do contato linguístico e de variação induzida por contato. Apesar da variação linguística induzida por contato não ser incomum, ela requer a descrição dentro de um modelo que torna possível contextualizar os dados linguísticos no espaço comunicativo. Isso requer a localização da variação da linguagem a partir do falante em seu contexto histórico (com seu repertório de variedades, com suas rotinas comunicativas e com o efeito dessas rotinas comunicativas em seu próprio repertório). Nesse sentido, o falante representa uma unidade mínima do espaço comunicativo (‘glossotope’) em que está inserido. — Artigo em inglês. — DOI: http://dx.doi.org/10.22409/gragoata.2017n42a920